The good doctor - Mates, Susan Onthank, 1950- (John Simmons short fiction award., 1994)
Twelve stories on healing. In the title story a doctor is seduced by a student, healing her of the complex of spinsterhood. In Julliard a music teacher who plays the cello cuts off a finger--so he can't play anymore--as atonement for failing a student for political reasons.